Interventions of the UNODC in Tackling Human Trafficking Issues in Thailand (2014-2017) - Muthia Jauza Delia; Muhammad Farid (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2025)
Thailand recorded a significant number of human trafficking cases during 2014-2015, leading to its classification as Tier Three (lowest tier) in the United States Department of State Trafficking in Persons Report. This classification subjected Thailand to international pressures. Subsequently, the classification had led the government of Thailand to formulate relevant policies to cope with the trafficking issues in the country. In this case, human trafficking itself is classified a threat to personal security accordingly to the concept of Human Security, which was developed by the UNDP in 1994. This study examines the UNDP 1994 Report’s concept of human security and Ian Hurd's International Organization Theory, focusing on the UNODC’s program from 2014-2017 to address transnational organized crime, particularly human trafficking. The research suggests that the UNODC as an international organization has made interventions as an actor, forum, and resource in promoting human security in Thailand. In this case, UNODC played the roles by assisting the government of Thailand through programs, which aimed to address human security issues, particularly personal security